Coordination and Differentiation of Strategies: The Impact on Farm Growth of Strategic Interaction on the Rental Market for Land - Anne Margarian (German Journal of Agricultural Economics (GJAE), 2010)
Among the family farms in Western Germany, regional differences in farm-development strategies can be observed. The land market has been identified in the literature as crucial for farm growth. In various studies, developments are driven by assumptions about the effects of scale and the initial heterogeneity of farms. In contrast, the present paper focuses on the potential role of opportunistic and future behaviour for the development of different farm strategies. In order to demonstrate the potentially crucial role of strategic behaviour, we introduce a thought experiment and focus on the theoretical case of identical farms. In the light of ideas from theories about oligopolistic markets, two central problems of decision-making are identified: the coordination problem of farm exits and the problem of strategic choices made by the remaining farms. This paper supplements explanations that argue on the basis of farms' heterogeneity in that it offers an approach to the question of why farms might not overcome their short-term constraints in order to realise strategic advantages in competition.
Keywords: 330